PP30 Primary Care Utilisation and its Socio-Economic Determinants: findings from the Lifeways Cross-Generation Cohort Study During the Recession Period in the Republic of Ireland. (10th September 2013) - Viljoen, K; Murrin, C; Segurado, R; O'Brien, J; Somerville, R; Khalil, H; Kelleher, C C
Abstract : Background: Worldwide there is a well-established association between rates of primary and secondary health care utilisation and socio-economic deprivation. The collapse of the Celtic Tiger economy and recession in 2006/7 may have had a significant impact on health care utilisation. Aim: To examine patterns of primary care utilisation rates in the Irish adult population and its determinants over a 10 year period. Setting: Lifeways is a Cross-Generation Cohort Study of 1082 families recruited initially in the East and West of Ireland. Data were collected by self-administered questionnaire at baseline 2001-3, in 2007 and 2011/12, and from general practitioners in 2003. At the fourth phase of follow-up in 2011 1588 adults in 592 families responded. Methods: Respondents provided data on health care utilisation (HCU), morbidity and socio-economic status at three time points and through GP notes. Recession impact was measured by standard questions and a composite economy score calculated (1–15, higher score indicating bigger impact). Rates of HCU were defined as 'Less frequent' < = 2 consultations/yr and 'More frequent' > = 3 consultations/yr. HCU was compared according to lineage, General Medical Services (GMS) means-tested eligibility to free health care, morbidity and various socio-economic indicators across the 4 time points. We subsequently fit a linear mixed effects model where family id and personal id were modelled as random effects with random intercepts for each family and random intercepts and slopes over time for each individual. Results: At each time point, a strong, significant age gradient was noted, with women (mothers and grandmothers) being the more frequent users than men. Grandparents showed an average of 15% higher utilisation than parents (Chi-sq, p < 0.0001). GMS eligibility remained the strongest predictor of HCU at all time points (Chi-sq 172.468, p < 0.0001). At baseline, those with difficulty getting by had significantly higher HCU rates 53.7% vs. 46.3% (Chi-sq 10.212, p < 0.0001). In the final mixed model, economy score, time, GMS eligibility and co-morbidity were all highly significant predictors of healthcare utilisation adjusted for age, sex and region. Significantly higher odds of healthcare utilisation at 10yr follow-up were demonstrated for those who are GMS eligible (OR 6.9 [95% CI 2.5, 19.1], p<0.0001). A significant decrease in the odds of utilisation with increasing economic stress was also evident (6.9 [0.5, 0.9], p=0.02). Conclusion: This analysis suggests persistent effects of morbidity characteristics on healthcare utilisation patterns. Exacerbated by the recent recession in adults in the Republic of Ireland.